VET in Europe - Country report Austria - Tritscher-Archan, Sabine [Herausgeber]; Nowak, Sabine [Herausgeber] (My University, 2011)
This report provides a comprehensive picture of the Austrian VET system. The focus is on VET programmes at the upper secondary level, i.e. on full-time school-based paths and dual vocational training (apprenticeship). In addition, VET programmes at post-secondary and tertiary levels are outlined as well as the available CVET paths. This report does not cover university programmes, which - according to Austrian HE legislation - primarily serve the purpose of pre-vocational qualification. (öibf, BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsbildungspolitik; Berufsausbildung; Berufliche Weiterbildung; Bildungspersonal; Bildungsfinanzierung